Rediscovery of Laura’s glassfrog Nymphargus laurae (Anura: Centrolenidae) with new data on its morphology, colouration, phylogenetic position and conservation in Ecuador - María José Sánchez-Carvajal; Grace C. Reyes-Ortega; Diego F. Cisneros-Heredia; H. Mauricio Ortega-Andrade (PeerJ, 2021)
We report the rediscovery of Laura’s Glassfrog, Nymphargus laurae Cisneros-Heredia & McDiarmid, 2007, based on two specimens collected at the Colonso-Chalupas Biological Reserve, province of Napo, Ecuador. The species was described and known from a single male specimen collected in 1955 at Loreto, north-eastern Andean foothills of Ecuador. Limited information was available about the colouration, systematics, ecology, and biogeography of N. laurae. We provide new data on the external morphology, colouration, distribution and comment on its conservation status and extinction risk. We discuss the phylogenetic relationships of N. laurae, which forms a clade together with N. siren and N. humboldti. The importance of research in unexplored areas must be a national priority to document the biodiversity associated, especially in protected areas.